Testing for economies of scope in European railways: an effciency analysis - Christian Growitsch; Heike Wetzel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
In this paper, we conduct a pan-European efficiency analysis to investigate the performance of European railways with a particular focus on economies of vertical integration. We test the hypothesis that integrated railways realize economies of scope and, thus, produce railway services with a higher level of efficiency. To determine whether joint or separate production is more efficient, we apply a Data Envelopment Analysis super-efficiency bootstrapping model which relates the efficiency for integrated production to a reference set consisting of separated firms which use a different production technology. We find that for a majority of European railways economies of scope exist.
Keywords: L22; L43; L92; 330; Schienenverkehr; Verbundvorteil; Wirtschaftliche Effizienz; Data-Envelopment-Analyse; Europa; EU-Staaten